2007
DOI: 10.1111/j.1365-2702.2007.01548.x
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary day surgery: patients’ experience of discharge and recovery

Abstract: The results and problems identified have applicability for the development of discharge planning services and patient education in a day surgery context. It is suggested that the use of evidenced-based and innovative interventions among health professionals might improve patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 18 publications
3
69
0
8
Order By: Relevance
“…The findings of this study support those of an earlier study (Heino, 2005, Fagermoen & Hamilton, 2006, Gilmartin, 2007 which showed that good quality counselling was focused on oral counselling, with written materials to support it. It is also known that patients are not so well oriented to counselling after anesthesia (Stomberg et al, 2008).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The findings of this study support those of an earlier study (Heino, 2005, Fagermoen & Hamilton, 2006, Gilmartin, 2007 which showed that good quality counselling was focused on oral counselling, with written materials to support it. It is also known that patients are not so well oriented to counselling after anesthesia (Stomberg et al, 2008).…”
Section: Discussionsupporting
confidence: 87%
“…In day surgery, patients also need counselling on the use of analgesics and pain assessment (Rhodes et al, 2006, Stomberg et al, 2008 counselling as well as on rehabilitation, such as knee extension and flexion, and in how to use mobility aids (such as crutches) and for how long (Pieper et al, 2006, Gilmartin, 2007 Patients also want to know about the possible complications (Gilmartin & Wright, 2008), nutrition (Rhodes et al, 2006, Fredericks et al, 2010 and what health changes are normal or not after surgery (Fagermoen & Hamilton, 2006). Having an opportunity to meet with healthcare staff after day surgery is important to patients (Rhodes et al, 2006, Gilmartin, 2007, Stomberg et al, 2008, Knier et al, 2015. Day surgery leads to emotional stress, such as anxiety and fear, counselling meaning that emotional counselling is also necessary (Hagberth, 2008, Stomberg et al, 2008, Gardiner et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations